SOFTWARE CONTRACTS - A Comparative Legal Analysis on Software Transactions in Germany, the United States, South Africa, and under the Convention on Contracts for the International Sale of Goods. - Briskorn, Nina (Department of Commercial Law, 2014)
I will examine the treatment of software under the contract laws of the United States, Germany, and South Africa. Furthermore I will analyse the existing international uniform contract law, the Vienna Convention on the International Sale of Goods. I will illustrate how the different legal structures are leading to legal uncertainty in software transactions. Some of the issues being considered include whether software should be treated the same, regardless of the mode of delivery, whether software can fit into existing legal concepts and whether there should be a new body of contract law for software, nationally and internationally. The analysis will be restricted to software transactions for the permanent use against single payment, as it is the common mode of transaction and poses the greatest difficulties. The focus will be on standard software. This term is used to describe computer programs manufactured as copies designed for a range of application for an unlimited number of users as opposed to custom designed software that is specifically designed for the needs of the customer.